PENYELESAIAN SENGKETA TANAH DARI SUKU SA’O NDE DI RITI (DONGGA) KABUPATEN NAGEKEO KECAMATAN NANGARORO, MENGGUNAKAN KEARIFAN LOKAL BHEDI WETI - Klara seke, Sonia; Kurniawan Geong, Mario Pietro; Don Rade, Stefanus (Gapenas Publisher, 2024)
This paper discusses the role of local wisdom, especially the **bhedi weti** tradition, in resolving disputes in the Sa'o Nde Tribe community. Through a case study involving Yohanes Ame KAE and Dongga Village, this study explores how bhedi weti functions as an effective and peaceful conflict resolution method. Bhedi weti not only emphasizes reaching an agreement between the disputing parties, but also respects individual rights and strengthens social relationships within the community. Values ??such as justice, communication, and respect for tradition are at the heart of this process, which involves the active participation of all members of the community. The conclusion of this study shows that the application of bhedi weti can provide a sustainable solution to conflict, as well as maintain harmony and cultural identity within the community. Thus, this paper highlights the importance of maintaining and integrating local wisdom in efforts to resolve modern social problems.